Correction: Nguyen et al. Oligonucleotide Solid Nucleolipid Nanoparticles against Antibiotic Resistance of ESBL-Producing Bacteria. Pharmaceutics 2022, 14, 299 - Phuoc Vinh Nguyen; Clémentine Aubry; Narimane Boudaoud; Alexandra Gaubert; Marie-Hélène Langlois; Mathieu Marchivie; Karen Gaudin; Corinne Arpin; Philippe Barthélémy; Tina Kauss (MDPI AG, 2022)
In the original publication [...]